Immune-related RNA signature predicts outcome of PD-1 inhibitor-combined GEMCIS therapy in advanced intrahepatic cholangiocarcinoma - Zeng, Tian-mei; Pan, Yu-fei; Yuan, Zhen-gang; Chen, Dong-sheng; Song, Yun-jie; Gao, Yong (Frontiers in Immunology, 2022)
Abstract Background: Immune checkpoint inhibitors (ICIs) combined chemotherapy in advanced intrahepatic cholangiocarcinoma have been proved more efficacy in a series of clinical trials. However, whether tumor microenvironment (TME) play a vital role in immune-combined therapy has not been rigorously evaluated. Methods: Firstly, we assayed the immunogenic properties of GEM-based chemotherapy. Then, twelve ICC patients treated with PD-1 inhibitor (sintilimab) combined gemcitabine and cisplatin (GemCis) from a phase 2 clinical trial (ChiCTR2000036652) were included and their immune-related gene expression profiles were analyzed using RNA from baseline tumor samples. Immune-related signature correlating with clinical outcome was identified according to the 12 ICC patients and its predictive value was validated in ICC cohort with 26 patients. Multiplexed immunofluorescence (mIF) and flow cytometry (FCM) analysis were performed to evaluate the immune-related molecules with therapeutic outcomes. Results: GEM-based chemotherapy induced immunogenic cell death of cholangiocarcinoma cells, together with increased CD274 expression. In ICC cohort we found upregulation of immune-checkpoint molecules and immune response-related pathways were significantly related to better clinical outcome. On the contrary, Baseline immune-cell proportions in tumor tissues did not show any correlation with clinical benefit between responders and non-responders. Immune-related signature (including 6 genes) correlating with clinical outcome was identified according to the 12 ICC patients and its predictive value was validated in a small ICC cohort with 26 patients. Conclusion: Immune-related RNA signature predicts outcome of PD-1 inhibitor combined GEMCIS therapy in advanced intrahepatic cholangiocarcinoma, which could be tested as a biomarker for immune-chemotherapy in the future.